Evaluation of possible application of CO2 capture technologies for Petrovietnam’s thermal power plants - Tran Thanh Phuong; Vo Hong Thai; Vu An; Hoang Mai Chi; Nguyen Thi Thu Hien (Petrovietnam Journal, 2013)
Petrovietnam’s activities in the electric power industry have strongly developed in recent years. In 2012, thetotal electricity produced and supplied to the national grid by Petrovietnam is 15.27 billion kWh, which is equivalent to 110.2% of the yearly plan and represents a 13.4% increase over the same period of 2011. Together with the development of its power projects, Petrovietnam is paying special attention to environmental protection, including reduction of emission of CO2, SOx, NOx, and dust from power plant projects. In this article, the authors present CO2 capture technologies for power plants and evaluate the possible application of those technologies for Petrovietnam’s thermal power plants.